Sistema IoT para prevenção de falhas e monitoramento remoto em ambientes termicamente controlados - Almeida, Rafael Dias Ribeiro de (2025)
The increasing use of technologies such as computers and the internet has revolutionized the way we interact, work, entertain ourselves, and manage our health. In this context, the Internet of Things (IoT) emerges as an innovation that connects a variety of devices and systems, aiming to enhance the daily experiences of users. Covering everything from lighting systems to appliances and entertainment solutions, IoT allows users to manage various aspects of their environment in an integrated and intelligent manner, using everything from smartphone apps to voice commands through virtual assistants. This project focuses on developing an IoT system for monitoring and detecting faults in thermal systems, combining electronics, microcontrollers, and sensors with machine learning methods. The goal is to integrate these technologies to create a device that monitors thermal conditions in real time while identifying abnormal patterns that may indicate potential failures. This predictive approach to the maintenance of heating and cooling systems aims to prevent disruptions before they occur, enhancing system efficiency and reducing operational and maintenance costs. At the conclusion of this project, experimental results will be compiled and presented, demonstrating the effectiveness of the proposed system. It is expected that the developed device will provide detailed information on the performance and operational conditions of the thermal systems. Furthermore, the implementation of this IoT monitoring system promises to enhance security and energy efficiency, also providing users with a robust tool for remote control and management of their environments, aligning technology and practicality in everyday life.